KINERJA APARATUR PEMERINTAH DESA DALAM PENGELOLAAN ADMINISTRASI DESA - Bron (Journal Ilmu Sosial, Politik dan Pemerintahan, 2015)
Good government village is depending on the performance of government village employee. Government village employee consist of: village head and staff that the most important person who in charge of managing the administration. Tumbang Kaman government village as the lowest unit of government have obligation to make good performance employee through administration management, therefore it has been granted as the champion of village competition in 2013. The research uses descriptive-qualitative methode. Collecting data technic is being done by observation, interview, and documentation. The data analysis technic uses interactive model by Miles and Huberman. Depend on the fact from the field, found some conclusion that: 1) Good government employee performance have achieved observed by quality, quantity, time work, and tim work. 2) Unsupporting factors in administration management was not meaningfull, but it still there: lower skill administration of the government village employee, the salary should be increase. Supporting factors are: the infrastructure are available well in Tumbang Kaman village and also tim work have achieved well.